Measuring the performance of innovation and entrepreneurship networks - Lopes, João Nuno Morais (2019)
This study proposes a performance measurement adjusted to the conceptual model "multiple helix ecosystem for sustainable competitiveness" (Peris Ortiz et al., 2016), supported in innovation and entrepreneurship networks, in order to contribute to the improvement of sustainable competitiveness of territories. A systematic literature review was carried out between the years 1900 and 2016, based on the study keywords. The proposed performance measurement model was conceived from the "Multiple Helix Ecosystem" concept, allowing its empirical verification applied to national and regional economies.